Qualidade fisiológica de sementes de palmeiras e inventário quali-quantitativo de 18 praças do município de São Carlos - SP - Negreiros, Gisele de Freitas (2004)
This work was done at São Carlos city, SP state. In the first and second chapter the experiments were carried out on the seed germination laboratory and experimental garden, from Botany Departament, at UFSCar. The objective of the first chapter was identify differences on seed quality, among four Palmae species, when submitted to accelerated aging. Dypsis lutescens, Euterpe edulis, Phoenix reclinata and Roystonea oleracea were exposed to 0;12; 24; 36 and 48 hours inside the camara at 45ºC and 100% of R.U. After, they were evaluated in relation to germination and seedling vigor in a green house. Dypsis lutescens and Euterpe edulis presented the great sensibility to adverse effects of accelerated aging. The period of 48 hours inside the aging camara was critical for the vigor parameters evaluated for Phoenix reclinata and Roystonea oleracea. The seed size influence on physiological quality and seedling development was determinated in the second chapter. Dypsis lutescens, Euterpe edulis, Euterpe oleracea and Phoenix reclinata were select in relation to seed size and 100 seeds weight. After, the germination and seedling vigor were analysed in a green house. Differences among the species were recorded in relation to the vigor parameter evaluated, and the influence of seed size was confirmed. In the third chapter, the objective was to develop a method to evaluated quail and quantitatively 18 squares from São Carlos city, including basic structures, green areas, conservation and Palmae species, as well as the square history. Several periodic visits were done and people opinion was recorded. Bibliography references, photography records since the past until now were add. The method employed allow to contrast the squares, the plant composition and the identification of Palmae elements. Among the squares were identify the genera: Phoenix, Syagrus, Roystonea, Archontophoenix, Caryota, Dypsis and Livistona. The squares that offer the better structure and green area for the people are: Coronel Paulino Carlos and Dr. Christiano Altenfelder Silva.